Physical Characterization of the Manganese-sensing Pneumococcal Surface Antigen Repressor (PsaR) from Streptococcus pneumoniae* - Lisher, John P. (2013)
Transition metals, including manganese, are required for proper virulence and persistence of many pathogenic bacteria. In Streptococcus pneumoniae (Spn), manganese homeostasis is controlled by a high affinity Mn(II) uptake complex, PsaBCA, and a constitutively expressed efflux transporter, MntE. PsaBCA expression is transcriptionally regulated by the DtxR/MntR family metalloregulatory protein pneumococcal surface antigen repressor (PsaR) in Spn. Here, we present a comprehensive analysis of the metal and DNA-binding properties of PsaR. PsaR is a homodimer in the absence and presence of metals and binds two manganese or zinc per protomer (four per dimer) in two pairs of structurally distinct sites, termed site 1 and site 2. Site 1 is likely filled with Zn(II) in vivo (K(Zn1)≥10(13) M(−1); K(Mn1)≈10(8) M(−1)). The Zn(II)-site 1 complex adopts a pentacoordinate geometry by x-ray absorption spectroscopy containing a single cysteine, and appears analogous to the Cd(II) site observed in S. gordonii ScaR. Site 1 is necessary but not sufficient for full positive allosteric activation of DNA operator binding by metals as measured by ΔG(c), the allosteric coupling free energy, since mutants in site 1 show intermediate ΔG(c). Site 2 is the primary regulatory site and governs specificity for Mn(II) over Zn(II) in PsaR, with ΔG(c)(Zn,Mn)>>ΔG(c)(Zn,Zn) despite the fact that Zn(II) binds site 2 with 40-fold higher affinity relative to Mn(II), i.e., K(Zn2)>K(Mn2). Mutational studies reveal that Asp7 in site 2 is a critical ligand for Mn(II)-dependent allosteric activation of DNA binding. These findings are discussed in the context of other well-studied DtxR/MntR Mn(II)/Fe(II) metallorepressors.